Export Profiles of Small Landlocked Countries : A Case Study Focusing on their Implications for Lesotho - Ng, Francis; Yeats, Alexander (World Bank, Washington, DC, 2014)
World Bank demographic and country characteristic statistics identify 16 small landlocked countries that are similar to Lesotho. The authors attempt to determine what useful policy information can be derived from the recent trade performance of these "comparators." Among questions they pose are whether the trade profiles of the comparators suggest potentially promising export ventures for Lesotho, do they indicate directions for a geographic diversification of trade, or do they suggest products in which Lesotho might acquire a comparative advantage. The authors also use U.S. partner country statistics to evaluate Lesotho's export performance in this major market. The U.S. data indicate Lesotho lost competitive export shares for about three-quarters of its major clothing products during the late 1990s. The data show these losses were primarily to the North America Free Trade Agreement (NAFTA) countries in the Caribbean. Lesotho was competing on basically equal terms and did not fare well. But it is generally held that the most efficient clothing exporters are in the Far East and not Latin America. Lesotho's difficulties in competing with the latter have worrisome implications for its ability to compete with East Asian exporters when the Multifiber Arrangement is phased out. The comparative advantage profiles of the landlocked comparator countries suggest Lesotho's options for a greatly needed export diversification may be wider than is assumed. One or more of the comparator countries developed a comparative advantage in 110 four-digit SITC (non-clothing) manufactures which are generally labor-intensive in production. Many of these goods should also be suitable for production and export by Lesotho. International production sharing often involves the importation and further assembly of components in developing countries. This activity can significantly broaden the range of new products in which a country can diversify. Statistics show many landlocked comparator countries have moved into component assembly operations, and it appears this activity could contribute to Lesotho's export diversification and industrialization. But the quality problems associated with Lesotho's trade statistics makes it impossible to determine the extent to which local production sharing is occurring. A special effort is needed to tabulate reliable statistics on Lesotho's current involvement in this activity. Finally, the authors attempt to determine how the commercial policy environment in Lesotho compares with that in other countries. Policymakers previously had difficulty in addressing this issue, but several recent efforts to compile comprehensive cross-country indices of the quality of governance and commercial policies now provide relevant information. These statistics suggest domestic commercial policies make Lesotho relatively less attractive to foreign investment than many other developing countries. Less than 20 percent of all Latin American countries have a domestic commercial environment judged to be inferior to that in Lesotho, while the corresponding share for East Asia is under 30 percent. Overall, almost 70 percent of all developing countries appear to pursue commercial policies that make them as, or more, attractive to foreign investment than Lesotho.